PREVALENCE OF BOVINE LEPTOSPIROSIS AT TWO LOCALITIES IN PUNO DURING THE DRY SEASON AND DETERMINATION OF RISK FACTORS - Fiorella Arias Ch., Fiorella Arias Ch. (2011)
Leptospirosis is a disease caused by a spirochet of the genus Leptospira. It is aworld-wide zoonotic disease with a great economic impact because of the importantlosses that causes to livestock farmers, especially in terms of reproduction performanceand milk yield loses. The objective of the study was to estimate the prevalence ofleptospirosis in bovines in two farms in the department of Puno, Peru: the ILLPA-INIAExperimental Station and Cardenas farm at Mañazo and its association with season andage. One hundred and sixteen serum samples collected during the dry season wereevaluated. Blood samples were collected to all animals in both farms. The MicroscopicAgglutination Test (MAT) was used for the detection of antibodies through a set of fourserovars (canicola, icterohaemorrhagiae, pomona, and hardjo). The total prevalencewas 2.6% while 1.3% corresponded to animals at ILLPA-INIA and 5.3% to animals atMañazo. The icterohaemorrhagiae was the only prevalent serovar and the level ofantibodies was 1:200. The results suggested a low prevalence of Leptospira sp. in thedry season in the area of study.